Respuesta :

(2,-16) should be the answer

Answer:

vertex = (2, - 16)

Step-by-step explanation:

given

f(x) = (x - 6)(x + 2) ← equate to zero to find the zeros

(x - 6)(x + 2) = 0

Equate each factor to zero and solve for x

x - 6 = 0 ⇒ x = 6

x + 2 = 0 ⇒ x = - 2

The vertex lies on the axis of symmetry which is situated at the midpoint of the zeros, hence

[tex]x_{vertex}[/tex] = [tex]\frac{6-2}{2}[/tex] = [tex]\frac{4}{2}[/tex] = 2

Substitute x = 2 into f(x) for corresponding y- coordinate of vertex

f(2) = (2 - 6)(2 + 2) = - 4 × 4 = - 16

vertex = (2, - 16)